Value Creation for Audio Learning Service of Working Age Population in Bangkok - Meechusup, Thananan (วารสารพัฒนาการเรียนการสอน มหาวิทยาลัยรังสิต, 2025)
The purposes of this research were as follows: 1) To study personal data on audio learning service, beneficial perception, cost-advantage perception, perception of other factors and value perception towards working age population in Bangkok. 2) To study and develop the causal model, value perception and value creation of service users of audio learning service in the working age population in Bangkok. 3) To study about the problems, obstacles and suggestions for the improvement and development of an audio learning service. 4) Examine the correlations between latent variables as well as developing a Parsimonious Model. The major findings were as follows: 1. Most of the respondents have perceived a value from the use of an audio learning service at a high level, especially for product value and personal value; this perception is considered to be at a high level in benefits especially for personal benefit and experience benefit; the perception is considered at a high level in cost advantage especially for time saving and energy saving and is also considered to be at a high level with regard to other factors, especially for quality of content and time constraint. 2. Most of the respondents advised this researcher that the problems and obstacles were related to personal problems due to their knowledge background and concentration abilities. Suggestions to enhance the audio learning service comprised the suggestions that a listening period should be offered of 11-15 minutes, the content should be related to personal development and the narration should be simplified for ease of understanding. 3. The results from the testing of six hypothesises were: examination and acceptance of the correlation between characteristics of the audio learning service and perception of functional benefits; the correlation between perceptions of cost-advantage; the correlation between percep- tion of other factors; the correlation between perceptions of functional benefit and value perception; correlation between perceptions of other factors and value perception; and finally, that there was no correlation between perception of cost-advantage and value perception because the hypothesis test showed rejection. 4. The causal model of value perception for audio learning service, resulting from factors and paths analysis, was valid and fitted the empirical data. All variables of the model accounted for 65.9% of the variance. Whilst there were hypotheses under the cost-benefit model, there was no correlation between perception of cost-advantage and value perception.